Effect of an acute bout strength training on executive function among college students: a pilot study - Jani, Priyaben A.; Verma , Neha (International Journal of Research in Medical Sciences, 2024)
Executive functions are built such as reasoning, problem solving and planning. Even mild form of executive dysfunction might hamper everyday activities depending on the work and situation, which requires various cognitive domains. Strength exercises are able to increase the anti-inflammatory balance with an increase in cognition and better physical performance. Aim of the study was to evaluate the acute bout effect of strength training on executive function among college students. 10 participants were divided into control and intervention group for experimental study performed at SPB physiotherapy college. Consent was taken from the participants. Only one session of 30 minutes was performed by intervention group. Intervention group performed 10 repetitions of 12 exercise per set and 2 sets per session. Warm up and cool down was performed by participants. Pre and post measures of trail making test B was recorded as outcome measure for executive function. Trail making test score was significantly improved immediately after strength training with p value <0.05 suggesting improvement in executive function. The study concluded that Strength training has greater immediate impact on executive function among college students